ANALISIS PERBANDINGAN KINERJA ANTARA PORTOFOLIO OPTIMAL MODEL MARKOWITZ DAN MODEL INDEKS TUNGGAL (COMPARATIVE ANALYSIS OF PERFORMANCE BETWEEN OPTIMAL PORTOFOLIO MARKOWTIZ MODEL AND SINGLE INDEX MODEL) - Laurimba Simorangkir (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2021)
The purpose of this study is to determine the composition of stocks, the amount of funding proportion, and optimal portfolio performance formed using Markowitz Model and Single Index Model and to determine whether there are differences in optimal portfolio performance established using Markowitz model and Single Index model based on real simulation or test based statistics. The population in this study is the stock of LQ-45 Group in Indonesia Stock Exchange with the number of selected samples of 30 stocks. Sampling is done by using purposive sampling method. This type of research is simulation and verifikatif (hypothesis testing). The data used are secondary data in the form of monthly stock price data from 2016 to 2019. The analysis technique used is descriptive with the application of portfolio analysis using Markowitz Model and Single Index Model. Hypothesis testing was done by using independent sample t-test. Based on the results of analysis on the real simulation of optimal portfolio performance formation found that the composition of stocks and the proportion of funds formed optimally there is a difference between the Markowitz Model and the Single Index Model, the optimal portfolio yield rate using the Markowitz Model is higher than the optimal portfolio yield using the Index Model Single, and optimal portfolio risk levels using the Markowitz model is higher than the optimal portfolio risk level using the Single Index Model. But statistically the test of optimal portfolio performance formed using Markowitz Model and Single Index Model is not significantly different.